Hierarchically structured nanowires on and nanosticks in ZnO microtubes - Rivaldo-Gómez, C. M. (Sci Rep, 2015)
We report both coaxial core-shell structured microwires and ZnO microtubes with growth of nanosticks in the inner and nanowires on the outer surface as a novel hierarchical micro/nanoarchitecture. First, a core-shell structure is obtained—the core is formed by metallic Zn and the semiconducting shell is comprised by a thin oxide layer covered with a high density of nanowires. Such Zn/ZnO core-shell array showed magnetoresistance effect. It is suggested that magnetic moments in the nanostructured shell superimposes to the external magnetic field enhancing the MR effect. Second, microtubes decorated with nanowires on the external surface are obtained. In an intermediate stage, a hierarchical morphology comprised of discrete nanosticks in the inner surface of the microtube has been found. Hyperfine interaction measurements disclosed the presence of confined metallic Zn regions at the interface between linked ZnO grains forming a chain and a ZnO thicker layer. Surprisingly, the metallic clusters form highly textured thin flat regions oriented parallel to the surface of the microtube as revealed by the electrical field gradient direction. The driving force to grow the internal nanosticks has been ascribed to stress-induced migration of Zn ions due to compressive stress caused by the presence of these confined regions.